Fruquintinib and sintilimab plus SOX as perioperative therapy for locally resectable advanced gastric/gastroesophageal junction adenocarcinoma: study protocol for a prospective, single-arm, phase II clinical trial - Meng, Xiangyu; Yang, Dong; Liu, Yuanlin; Wang, Chao; Yao, Junqiao; Zhang, Tao (Frontiers in Immunology, 2025)
BackgroundLocally advanced gastric/gastroesophageal junction (G/GEJ) adenocarcinoma faces high recurrence risks despite radical surgery. Perioperative chemotherapy (e.g., FLOT regimen) improves survival but has limited pathological complete response (pCR) rates and significant toxicity. Immunotherapy and anti-angiogenic agents show promise in advanced G/GEJ cancer. This trial evaluates fruquintinib (a VEGFR-1/2/3 inhibitor), sintilimab (PD-1 inhibitor), and SOX (oxaliplatin+S-1) as perioperative therapy for resectable locally advanced G/GEJ adenocarcinoma.MethodsThis prospective, single-arm, phase II trial (N = 25) enrolls treatment-naïve adults (18–75 years) with histologically confirmed, resectable cT3-4aN+M0 G/GEJ adenocarcinoma (AJCC 8th edition). Patients receive 3 cycles of neoadjuvant therapy:Fruquintinib:4 mg orally, days 1–14 (21-day cycle). S-1: 80–120 mg orally twice daily (based on BSA), days 1–14. Oxaliplatin: 130 mg/m² IV, day 1. Sintilimab: 200 mg IV, day 1.Radical gastrectomy with D2 lymphadenectomy follows 4–6 weeks post-neoadjuvant therapy. Adjuvant therapy (3 cycles of sintilimab for pCR patients; 3 cycles of preoperative regimen for non-pCR) starts 4–6 weeks post-surgery. Endpoints: Primary: pCR rate (ypT0/Tis ypN0 per CAP criteria). Secondary: R0 resection rate, major pathological response (MPR, ≤10% residual tumor), 2-year event-free survival (EFS), 2-year overall survival (OS), safety (NCI CTCAE v5.0). Exploratory: Biomarker analysis of tumor microenvironment. Statistical Analysis: Sample size (25 patients) was calculated using Fisher’s exact test (one-sided α = 0.05, power = 80%), assuming pCR improvement from 5% (historical control) to 20%. Efficacy analyses use intention-to-treat (ITT) population; safety analyses include patients receiving ≥1 neoadjuvant dose.DiscussionThis is the first trial combining fruquintinib, sintilimab, and SOX in perioperative G/GEJ cancer. If successful, it may expand treatment options for locally advanced disease. Limitations include single-arm design and small sample size.Trial RegistrationChinese Clinical Trial Registry (ChiCTR2400084194)